1977
DOI: 10.1002/path.1711230304
|View full text |Cite
|
Sign up to set email alerts
|

Cytolethal effects of glucocorticoids in human lymphoblastoid cell lines

Abstract: Glucocorticoid hormones penetrate rapidly into intact lymphoblastoid cells and are retained with the same high affinity and specificity as with cytoplasmic extracts. Optimal conditions for lethal glucocorticoid responses in vitro were determined for a series of human lymphoblastoid cell lines by using different glucocorticoid preparations, and steroid solvents and by varying the cell density. Kinetic studies revealed that lethal glucocorticoid effects are dose-dependent and that continuous exposure of cells to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

1978
1978
1999
1999

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 16 publications
(9 reference statements)
0
7
0
Order By: Relevance
“…4). The concentration of glucocorticoid used in these studies should saturate Ͼ90% of the cytosolic receptors (36). We find furthermore that the anti-glucocorticoid RU38486 (100 nM) substantially blocks the action of dexamethasone, restoring the inductions (Fig.…”
Section: Resultsmentioning
confidence: 63%
“…4). The concentration of glucocorticoid used in these studies should saturate Ͼ90% of the cytosolic receptors (36). We find furthermore that the anti-glucocorticoid RU38486 (100 nM) substantially blocks the action of dexamethasone, restoring the inductions (Fig.…”
Section: Resultsmentioning
confidence: 63%
“…Previous work (Bird et al, 1977;Barret et al, 1981) comparison of CCRF/CEM and CCRF/CEM-C7 did show an increased binding of prednisolone by C7 but not of dexamethasone . Now we are aware of the instability of diploid susceptible clones, changes in glucocorticoid binding together with other parameters will be monitored during reversion to the resistant state.…”
Section: Discussionmentioning
confidence: 83%
“…Several workers have employed HLCL to study the mechanisms of glucocorticoid-induced cell death in human lymphoid cells (Bird et al, 1975(Bird et al, , 1977Norman & Thompson 1977;Robertson et al, 1978;Burrow et al, 1981;Barrett et al, 1981; see also Munck & Crabtree, 1981). One of the problems encountered in such studies has been the lack of synchronization in response of cells to glucocorticoid treatment.…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies with a large series of human lymphoid cell lines (2)(3)(4)(5)(6) and freshly isolated leukemia cells from patients with chronic lymphocytic and hairy-cell leukemia (7), it was found that human lymphoid cells are remarkably resistant to the cytolethal and cytostatic effects of glucocorticoids in uitro despite the presence of substantial levels of cytoplasmic glucocorticoid receptors and evidence of uptake and binding of glucocorticoid by target cells. In nearly every case lymphoid cells required exposure to suprapharmacological concentration ( M) of steroid for prolonged periods (>48-72 h) before significant cytolethal or cytostatic responses resulted.…”
mentioning
confidence: 99%